PENYULUHAN PENDIDIKAN POLITIK MAHASISWA UMMAT MENJADI PEMILIH CERDAS MENUJU INTEGRITAS PEMILU 2024 - Maemunah Maemunah; Isnaini Isnaini (JURNAL PENGABDIAN MANDIRI, 2023)
The aim of implementing this service is to provide strengthening and political education to students at the Faculty of Teacher Training and Education, Muhammadiyah University of Mataram towards intelligent returning voters ahead of the 2024 simultaneous elections. The method used is a socialization and counseling approach. The results of socialization and political education outreach to students to become smart voters towards the integrity of the 2024 election which was held in the hall of the Faculty of Teacher Training and Education, Muhammadiyah University of Mataram. With political education outreach, it is hoped that every student will not only know but also become a citizen who has political awareness to be able to carry out responsibilities as demonstrated by changes in attitudes and increased levels of participation in the world of politics.